A robust bi-objective uncertain green supply chain network management - Golpîra, Hêriş (Serbian Journal of Management, 2016)
Many supply chain problems involve optimization of various conflicting objectives. This paper formulates a green supply chain network throughout a mixed integer linear problem with uncertain demand and stochastic environmental respects level. The first objective function considers minimization of supply chain costs while the second objective function minimizes CO2 emission level. Conditional Value at Risk (CVaR) approach is used to deal with demand uncertainty in compliance with data driven approach, employed to deal with the stochastic level of CO2 emission. The implementation of the proposed model has been demonstrated using some randomly selected numbers and the results are analyzed accordingly.